2006
DOI: 10.3748/wjg.v12.i5.739
|View full text |Cite
|
Sign up to set email alerts
|

Microproteinuria in patients with inflammatory bowel disease: Is it associated with the disease activity or the treatment with 5-aminosalicylic acid

Abstract: Microproteinuria is mainly associated with UC and its activity but not affected by 5-ASA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…We found no statistically significant association between baseline microalbuminuria and the occurrence of a relapse of CD. This is in contrast with the study by Mahmud et al [1] that shows a strong correlation between microalbuminuria and clinical markers of disease activity, but in agreement with others [12,13,14]. The differences could be attributed to varied disease activity and number of relapses.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…We found no statistically significant association between baseline microalbuminuria and the occurrence of a relapse of CD. This is in contrast with the study by Mahmud et al [1] that shows a strong correlation between microalbuminuria and clinical markers of disease activity, but in agreement with others [12,13,14]. The differences could be attributed to varied disease activity and number of relapses.…”
Section: Discussionsupporting
confidence: 84%
“…Due to the low rate of relapses, we could not evaluate the severity of microalbuminuria during relapse. Different studies have shown that microalbuminuria is present in a considerable percentage, between 6 and 12.9% of IBD patients showing higher concentration in active disease [1,2,13]. Normally, this reflects renal glomerular damage, but in IBD it could reflect an extraintestinal manifestation of the disease [6,18,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Poulou reported that subclinical renal damage was caused by IBD itself and not by 5-ASA. 19 A more recent review in 2007 concluded that 5-ASA nephrotoxicity seems to be idiosyncratic in nature rather than dose related to 5-ASA and exceptional. 20 In our study there was no difference concerning the intake of 5-ASA between the patients with RI and the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, microalbuminuria values have been shown to fall when the disease is quiescent, 9,10 even though the patients were receiving 5-ASA treatment. 14 A recent observational prospective study revealed that renal impairment was observed in 2.2% of 1529 IBD patients followed for 1 year, both including patients with and without concomitant 5-ASA treatment. 16 More recently, a case-control analysis found that IBD patients who were 5-ASA users had an increased risk of renal disease.…”
Section: Proteinuria In Patients With Ibdmentioning
confidence: 99%